Predicting IDH mutation status in grade II gliomas using amide proton transfer‐weighted (APTw) MRI. Issue 3 (16th July 2017) - Jiang, Shanshan; Zou, Tianyu; Eberhart, Charles G.; Villalobos, Maria A.V.; Heo, Hye‐Young; Zhang, Yi; Wang, Yu; Wang, Xianlong; Yu, Hao; Du, Yongxing; van Zijl, Peter C.M.; Wen, Zhibo; et al.
Abstract : Purpose: To assess the amide proton transfer‐weighted (APTw) MRI features of isocitrate dehydrogenase (IDH)‐wildtype and IDH‐mutant grade II gliomas and to test the hypothesis that the APTw signal is a surrogate imaging marker for identifying IDH mutation status preoperatively. Methods: Twenty‐seven patients with pathologically confirmed low‐grade glioma, who were previously scanned at 3T, were retrospectively analyzed. The Mann‐Whitney test was used to evaluate relationships between APTw intensities for IDH‐mutant and IDH‐wildtype groups, and receiver operator characteristic (ROC) analysis was used to assess the diagnostic performance of APTw. Results: Based on histopathology and molecular analysis, seven cases were diagnosed as IDH‐wildtype grade II gliomas and 20 cases as IDH‐mutant grade II gliomas. The maximum and minimum APTw values, based on multiple regions of interest, as well as the whole‐tumor histogram‐based mean and 50th percentile APTw values, were significantly higher in the IDH‐wildtype gliomas than in the IDH‐mutant groups. This corresponded to the areas under the ROC curves of 0.89, 0.76, 0.75, and 0.75, respectively, for the prediction of the IDH mutation status. Conclusion: IDH‐wildtype lesions typically were associated with relatively high APTw signal intensities as compared with IDH‐mutant lesions. The APTw signal could be a valuable imaging biomarker by which to identify IDH1 mutation status in grade II gliomas. Magn Reson Med 78:1100–1109, 2017. © 2017 International Society for Magnetic Resonance in Medicine.